A new collection of freshwater crabs from northern Madagascar with the description of a new species of Hydrothelphusa A. Milne-Edwards, 1872 (Brachyura: Deckeniidae: Hydrothelphusinae) - Cumberlidge, Neil; Robinson, Grace E.; Daniels, Savel R. (Zootaxa, 2025)
A recent collection of freshwater crabs from the Sava and Diana regions in northern Madagascar was examined. The specimens were assigned to five species, one of which is new to science and described here. This raises the number of species of freshwater crabs found in Madagascar to 27. All are endemic to the island and belong to the Afrotropical family Deckeniidae Ortmann, 1897, subfamily Hydrothelphusinae Bott, 1955. The new species, Hydrothelphusa sava sp. nov., is compared to the other species in this genus. It is distinguished from the other four congeners by characters of the carapace and cheliped and by molecular evidence. A map showing the distribution of the new species, and an updated key to the species of Hydrothelphusa A. Milne-Edwards, 1872 are provided. The other specimens reported herein belong to four species, most of which are from new localities: Hydrothelphusa agilis A. Milne-Edwards, 1872, H. madagascariensis A. Milne-Edwards, 1872, Madagapotamon humberti Bott, 1965 and Vahatra ambohitra (Cumberlidge & Meyer, 2009).